Sistem Informasi Manajemen Musik (SI MUSIK) - Humaira Kudadiri, Zahra (UNIVERSITAS SERAMBI MEKKAH, 2025)
Managing K-POP music playback is often done manually or using basic applications that are not specifically designed for this purpose. This process can be inefficient and prone to errors, especially when dealing with a large music catalog, including songs, albums, and artists. Additionally, the lack of an integrated system makes it difficult for users to search and play songs efficiently, such as finding tracks by album, artist, or specific themes. With the growing global popularity of K-POP, the need for a reliable and structured system to manage music playback has become increasingly important. This study introduces SIMUSIK (Music Management Information System), a system designed to simplify the management of K-POP music data and playback. SIMUSIK allows for the structured recording of song, album, and artist data while supporting direct music playback through a user-friendly interface. Users can quickly search for songs based on artist, album, or other categories, creating a more organized and efficient music playback experience. Specifically designed to meet the needs of K-POP fans, SIMUSIK offers features such as catalog management, playlist creation, and grouping songs by album or artist. By addressing the inefficiencies of manual methods, this system ensures faster and more accurate access to music data and playback functionality.